CHARACTER BUILDING: AN ANSWER TO THE WORSENING OF HUMAN CHARACTER? - Imam Tabroni; Rendy Afrizal; Elsa Nurmawati; Siti Nurlatifah (Pusat Riset dan Inovasi Nasional, 2021)
It has become public awareness that education is a means that human beings use throughout their lives to transmit and transform values as well as knowledge. Due to its strategic roles in transmitting and transforming values and knowledge, education also plays a very important role in instilling and developing the nation's character. Character education is important for the human's life so that the role education plays is not only limited to showing moral knowledge but also loving and willing to take moral actions.